1959
DOI: 10.6028/jres.063a.008
|View full text |Cite
|
Sign up to set email alerts
|

Precise coulometric titration of acids and bases

Abstract: Apparatus and techniques a re dc~crib ed for t h e t itration of acids a nd. bases by co nstantcurrent coulometry. The precision nnd accuraey of t he method aI~e JndLcated by tl traL lons of benzoic acid, potass ium acid pMhalate, adL piC aCld, hy droc~lo l'l c aCid, ~nd sod ium eal'-bon ate. Standard deviations of ± 0 .003 p er cent h ave been obtaIn ed which LndlCatp. that the reli abili ty of th e method is eq ua l to or exceeds t h at of class Ica l analytlcfLI proced ures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1966
1966
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 6 publications
(9 reference statements)
0
41
0
Order By: Relevance
“…The technique for precise coulometric titration of acids and bases has been worked out previously by Taylor and Smith [43]. The facilities used in this work were part of the equipment of the Micro chemical Analysis Section and have been described and illustrated in the annual report of that section for the year 1965 [44].…”
Section: Response Of the Glass Electrode In Heavy Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The technique for precise coulometric titration of acids and bases has been worked out previously by Taylor and Smith [43]. The facilities used in this work were part of the equipment of the Micro chemical Analysis Section and have been described and illustrated in the annual report of that section for the year 1965 [44].…”
Section: Response Of the Glass Electrode In Heavy Watermentioning
confidence: 99%
“…43 ix LIST OF TABLES (con't) The total area provided for the Section was a little more than 3,600 square feet of which slightly less than 300 square feet were given over to the activities of the Section Office.…”
mentioning
confidence: 99%
“…Based on Faraday's law, the coulometric assay yields the precipitation reaction factors on an absolute basis without any chemical standards, and highly precise results compared with other chemical methods. There are some reports regarding a coulometric study for acidimetric standards, [3][4][5][6][7][8] oxidimetric-reductometric standards, [9][10][11][12][13][14] and precipitation standards. [15][16][17][18][19][20][21] Hioki et al reported on the dependence of the coulometric titration results on the amount of sample mass due to the influence by carbon dioxide for acidimetry.…”
Section: 2mentioning
confidence: 99%
“…The acid was prepared in 0.45-m NaCl to yield a total ionic strength similar to that of seawater salinity 35.0 (I = ~0.7 M). The acid was standardized by coulometry (Taylor and Smith 1959;Marinenko and Taylor 1968). The acid molality was also checked by titration on seawaters with known alkalinities, and subsamples were sent to the laboratory of A. Dickson at SIO for an independent laboratory determination of the molality.…”
Section: Total Alkalinity Measurementsmentioning
confidence: 99%